Associations of neutrophil/high-density lipoprotein cholesterol ratio with frailty and its mortality - Zhang, Jianqiang (Frontiers in Endocrinology, 2025)
BackgroundFrailty is an increasingly important determinant in the field of health, and its identification has important clinical significance in the field of critical care medicine. However, there are still a large number of challenges in quick and accurate identification of frailty. This study aims to evaluate the value of the neutrophil/high-density lipoprotein cholesterol ratio (NHR) in frailty and its long-term survival.MethodsAdult participants from seven study cycles of the National Health and Nutrition Examination Survey (NHANES) database were included. Frailty was assessed with a 49-item Frailty Index (FI). Weighted logistic regression, restricted cubic spline (RCS), and Cox regression were used to analyze the association of NHR with frailty and its long-term survival. In addition, subgroup and interaction analyses were also performed.ResultsA total of 34,382 adult participants aged 47.6 on average were included, and 16,950 (48.8%) of them were males. After the adjustment of potential confounding variables, an increase of one standard deviation (SD) in NHR resulted in the increase of the incidence of frailty by 11% (OR: 1.11, 95% CI: 1.04-1.18, P = 0.002). RCS showed a J-shaped association between NHR and frailty, which was robust in all subgroups according to the subgroup analysis. In addition, the survival analysis revealed that NHR was significantly positively associated with all-cause (HR: 1.12, 95% CI: 1.07-1.17, P < 0.0001), cardiocerebrovascular disease (CCD)-specific (HR: 1.21, 95% CI: 1.11-1.33, P < 0.0001), and cancer-specific mortality risks (HR: 1.13, 95% CI: 1.07-1.19, P < 0.0001) in frail individuals.ConclusionIn the American adult population, NHR maintains a J-shaped relationship with frailty. In addition, NHR can help predict long-term mortality in frail individuals. This study demonstrates that NHR may become an effective predictor of frailty and its mortality.